2007
DOI: 10.1634/theoncologist.12-6-690
|View full text |Cite
|
Sign up to set email alerts
|

Review: Implications of In Vitro Research on the Effect of Radiotherapy and Chemotherapy Under Hypoxic Conditions

Abstract: LEARNING OBJECTIVESAfter completing this course, the reader will be able to:1. Argue why hypoxic regions in solid tumors often contain viable cells that are intrinsically more resistant to treatment with radiotherapy or chemotherapy.2. Describe how exposure of cells or cell lines to hypoxic conditions has major implications on multiple intracellular pathways.3. Evaluate the importance of investigating chemoradiotherapy combinations in vitro under both normoxic and hypoxic conditions.Access and take the CME tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 177 publications
(237 reference statements)
0
83
0
2
Order By: Relevance
“…However, our observations are consistent with our a priori hypothesis, grounded on evidence from recent in vitro and animal studies on the effects of hypoxia in cancer progression. Cancer cells subjected to either chronic (8)(9)(10) or intermittent hypoxia (11) show increased resistance to therapy (e.g., radiation) and malignant progression. Furthermore, recent experiments in a melanoma-injected mouse model demonstrate that intermittent hypoxia mimicking sleep apnea in humans increases tumor growth (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our observations are consistent with our a priori hypothesis, grounded on evidence from recent in vitro and animal studies on the effects of hypoxia in cancer progression. Cancer cells subjected to either chronic (8)(9)(10) or intermittent hypoxia (11) show increased resistance to therapy (e.g., radiation) and malignant progression. Furthermore, recent experiments in a melanoma-injected mouse model demonstrate that intermittent hypoxia mimicking sleep apnea in humans increases tumor growth (12).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypoxia, a common feature in solid tumor tissue, has been associated with therapeutic resistance, tumor progression, and metastatic potential (8)(9)(10). In vitro studies have further demonstrated that cultured lung cancer cells subject to intermittent hypoxia are more resistant to radiation and apoptosis and are more prone to metastasis (11).…”
mentioning
confidence: 99%
“…45,46 Therefore, the use of CDK inhibitors to reduce HIF-1 activity may be a useful strategy in combination with therapies that are currently used in the clinic. Here, we show that inhibition of CDK1 and CDK4 dramatically reduces HIF-1 activity in both normoxic and hypoxic environments.…”
Section: Cdk Inhibition As a Strategy To Oppose Hif-1 In Cancermentioning
confidence: 99%
“…Hypoxia and HIF-1 contribute to the poor response to anticancer therapy by several mechanisms (Cosse and Michiels, 2008;Tredan et al, 2007;Wouters et al, 2007). Indeed, HIF-1 activation allows expression of a battery of genes involved in survival and cell resistance to chemotherapy.…”
Section: Hif-1 and Hif-target Genes: Actors For Drug Resistancementioning
confidence: 99%